2012
DOI: 10.1142/s0219876212500417
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Strength Reduction Dda Method and Its Application to Mountain Tunnel

Abstract: The stability of tunnel surrounding rock is the mainly concerned content during tunnel design and construction procedure. It is one of the main tasks for researchers to accurately estimate the stability of tunnel surrounding rock. Generally, determined by its engineering geological features, surrounding rock of mountain tunnel is cut by joints into discontinuous blocks, which can be more accurately analyzed by discontinuum-base numerical methods, e.g., the discontinuous deformation analysis (DDA) method. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…They deduced the displacement analysis formula of tunnel surrounding rock by using the generalized Hoek-Brown strength criterion, which makes the calculation results more suitable for the actual tunnel deformation. Xia et al [22] used the strength reduction method and catastrophe theory to study the stability of surrounding rock and applied the research theory to practical engineering, which achieved good results. Wu et al [23] combined the Levenberg-Marquardt optimization technique with complex variable differential method and proposed a modified optimization technique for stress-seepage coupling problem, which can accurately and effectively estimate multiple rock mass parameters.…”
Section: Introductionmentioning
confidence: 99%
“…They deduced the displacement analysis formula of tunnel surrounding rock by using the generalized Hoek-Brown strength criterion, which makes the calculation results more suitable for the actual tunnel deformation. Xia et al [22] used the strength reduction method and catastrophe theory to study the stability of surrounding rock and applied the research theory to practical engineering, which achieved good results. Wu et al [23] combined the Levenberg-Marquardt optimization technique with complex variable differential method and proposed a modified optimization technique for stress-seepage coupling problem, which can accurately and effectively estimate multiple rock mass parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Catastrophe theory became widely used due to the efforts of Zeeman [19] and Arnold and Afraimovich [20]. Recently, several researchers applied catastrophe theory to analyze stability problems in geology and geomechanics [21][22][23]. Pan et al [21] established a fold catastrophe model of a tunnel rock burst and reported that the occurrences of a rock burst are related to both the ratio of the elastic modulus to the descendent modulus of the rock mass and the rock mass crack growth degree.…”
Section: Introductionmentioning
confidence: 99%
“…Based on fold catastrophe theory, Miao et al [22] presented a model of a seepage flow system to analyze the dynamical behavior of water or gas flows in damaged rock, and the influences of different key parameters on the stability of seepage flow systems were obtained. Using catastrophe theory and the discontinuous deformation analysis (DDA) method, Xia et al [23] studied the stability of tunnel surrounding rock and obtained the safety factors for tunnels, which can be adopted in real-life projects to guarantee the safety of the tunnels.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods are used to simulate local discontinuous problem, such as FEM (finite element method) [2,3], DEM (discrete element method) [4,5], and DDA (discontinuous deformation analysis) [6][7][8][9], but there are more or less disadvantages in computational efficiency. Although there are some reports about stability analysis by using SRM based on these methods, the failure criteria need to be improved [10][11][12].…”
Section: Introductionmentioning
confidence: 99%